Analysis of influence factors audit delay (Study at KAP in Surabaya and Malang) - Novika Hendarmoko (Central Research Institute for Agriculture (CeRIA), 2021)
The purpose of this study was to find out whether the factors of company size, auditor opinion on company financial statements, KAP size, length of time the company has been a KAP client, quality of assigned KAP auditor staff, level of company internal control and post-employment benefits (actuarial) have an effect on audit delay both jointly or partially referring to primary data in the form of KAP auditor opinion in Surabaya and Malang. Audit delay is the length of time for audit completion as measured from the closing date of the financial year to the date of issuance of the audit report. This audit delay results in reduced benefits of the contents contained in the financial statements. This research was conducted in Surabaya and Malang. Data collection was carried out by giving questionnaires to respondents. The number of questionnaires distributed was 90 questionnaires to auditors at KAPs that were officially registered in Surabaya and Malang. The collected data will then be processed using the SPSS 12.0 program and analyzed using the regression method. Two important things that must be considered by investors in investing in the capital market are the expected benefits and risks that may occur. Along with the increasing number of companies going public in Indonesia, the demand for financial statement audits is also increasing. Therefore, financial reports audited by independent auditors must be published within a predetermined time. Conversely, if the financial statements audited by independent auditors are published beyond the specified time, then the audited financial statements experience audit delay. The test results using the F test show that all the factors studied together have a significant effect on the Audit Delay variable. While the results of the t test show that all the factors studied also have a significant positive effect on the Audit Delay variable.